Family Husbandry in the Tropical Island of Mayotte: Struggling for Autonomy from Production to Sanitary Problems - Jacques Cabaret; Sittirati Mohamed; Fabrice Guégnard; Claude L. Charvet; Cédric Neveu; Mohamed Issouf (Animals)
Mayotte is a small tropical island in the Comoros archipelago. It became recently a French department and much of its food, especially meat, is imported from abroad. The development of livestock farming is therefore a necessity. To understand the problems faced by Mahoran farmers, we organised semi-directive interviews with 15 farmers who reared cattle, sheep, goats or poultry. The first difficulty of farmers was limited access to land, especially for ruminants. This led to feed shortages. Another difficulty was the limited access to water and the poor quality of the roads to reach the farms. Poultry farmers were too dependent on importations of feed and laying hen or broiler genotypes from metropolitan France. The lack of organization for independent food productions (absence of abattoirs, cooperatives or organised markets) is also an obstacle to the development of the sector. Animal health, although not considered a major problem, has been a nuisance in the past (anthrax in cattle or salmonella in poultry). Mahoran farmers trust veterinarians or their assistants to manage health, although they complain about the high cost. Surprisingly, farmers use traditional medicine for many of their ailments, mostly based on local plants, but rarely for animals. Overall, our study reveals that larger land areas, better availability of money for investment and access to water and fodder are urgently required to improve livestock production and economic viability of farmers in Mayotte.